2005
DOI: 10.1111/j.1468-2982.2005.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial Cluster Headache. Is Atypical Cluster Headache in Family Members Part of the Clinical Spectrum?

Abstract: Familial cluster headache (CH) was analysed in 21 Swedish families. Diagnosis was made according to The International Classification of Headache Disorders 2004. We identified 55 affected, of whom 42 had episodic or chronic CH, one had probable CH and 12 had atypical symptoms. The atypical cases did not fulfil the diagnostic criteria for CH, but had clinical symptoms with more resemblance to CH than to migraine or other trigeminal autonomic cephalgia syndromes. The overall male : female ratio was 1.8:1. The ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…Therefore, it seems likely that progression of age is not the major factor in the development of cluster in migraine headache patients. The overall prevalence of migraine in patients with CH is comparable to that seen in the general population [24].…”
Section: Evolution Of Migraine To Clustermentioning
confidence: 63%
“…Therefore, it seems likely that progression of age is not the major factor in the development of cluster in migraine headache patients. The overall prevalence of migraine in patients with CH is comparable to that seen in the general population [24].…”
Section: Evolution Of Migraine To Clustermentioning
confidence: 63%
“…However, this may also be compounded by intra-familial clinical variability and presence of phenotypes atypical for CH. The documented preponderance of relatives with atypical CH in these studies complicates this further [39,40]. These cases are often omitted from epidemiological studies as they do not strictly fulfil diagnostic criterion, but perhaps represent part of a clinical spectrum associated with intergenerational genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Whichever genes turn out to be involved, there may be a predisposition toward anticipation. As mentioned earlier, a study by Sjostrand [23] demonstrated a signifi cantly lower mean age of onset in the second/third generation of families with CH than in the fi rst generation.…”
Section: Geneticsmentioning
confidence: 85%
“…When looking at a familial cluster population, the mean age of onset was signifi cantly lower in the second and third generation (22 years) than in the fi rst generation (31 years), suggesting either genetic anticipation or selection/diagnosis bias to account for earlier age of presentation [23].…”
Section: Age Of Onsetmentioning
confidence: 99%